2018
DOI: 10.1016/j.immuni.2018.09.024
|View full text |Cite|
|
Sign up to set email alerts
|

Successful Anti-PD-1 Cancer Immunotherapy Requires T Cell-Dendritic Cell Crosstalk Involving the Cytokines IFN-γ and IL-12

Abstract: Anti-PD-1 immune checkpoint blockers can induce sustained clinical responses in cancer but how they function in vivo remains incompletely understood. Here, we combined intravital real-time imaging with single cell RNA sequencing analysis and mouse models to uncover anti-PD-1 pharmacodynamics directly within tumors. We showed that effective antitumor responses required a subset of tumor-infiltrating dendritic cells (DCs), which produced interleukin 12 (IL-12). These DCs did not bind anti-PD-1 but produced IL-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
594
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 733 publications
(665 citation statements)
references
References 62 publications
33
594
1
2
Order By: Relevance
“…The field of cancer immunotherapy and checkpoint blockade has focused largely on direct effects on T cells. In this issue of Immunity, Garris et al (2018) show that the efficacy of anti-PD-1 therapy depends on a T-celldendritic-cell (DC) licensing loop fueled by IFN-g and IL-12, thereby establishing a central role for DCs in promoting anti-cancer T cell immunity during checkpoint blockade.…”
mentioning
confidence: 99%
“…The field of cancer immunotherapy and checkpoint blockade has focused largely on direct effects on T cells. In this issue of Immunity, Garris et al (2018) show that the efficacy of anti-PD-1 therapy depends on a T-celldendritic-cell (DC) licensing loop fueled by IFN-g and IL-12, thereby establishing a central role for DCs in promoting anti-cancer T cell immunity during checkpoint blockade.…”
mentioning
confidence: 99%
“…There is considerable evidence that combining PD‐1‐targeted therapies with other immunotherapy agents will cause improved outcomes compared to monotherapy activity. For this purpose, several cytokines are being tested to overcome the resistance mechanisms by expanding and reactivating effector NK and T lymphocytes and promoting the shift of lymphocytes to the tumor environment (Dai et al, 2016; Desbois et al, 2016; Garris et al, 2018; Zhao et al, 2018). Cytokine‐based drugs combined with PD‐1/PD‐L1 inhibitors have had some excitement clinical results in several ongoing clinical trials (as shown in Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has demonstrated a critical role for the CD28/B7 pathway in the proliferative rescue of CD8 + T cells and the enhanced control of tumor growth by PD-L1 blockade in mice 32 . Moreover, it was shown that intratumoral cDC1-derived IL-12 activates CD8 + TILs and contributes for effective PD-1 blockade therapy 27 . Given the various avenues through which cDC1-CD8 T cell crosstalk could be established, future studies will need to determine precisely how cDC1s elicit robust CD8 T cell responses during αPD-1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-infiltrating cDC1s traffic tumor antigens to the tumor draining lymph node (TDLN) in a CCR7-dependent manner where they efficiently cross-prime tumor-specific naive CD8 + T cells 21,22,23 . In addition to mediating the induction of endogenous anti-tumor immune responses, recent studies have implicated an important role for cDC1s in the efficacy of checkpoint blockade therapy 24,25,26,27 . In particular, it was shown that tumor-bearing mice that were developmentally deficient in BATF3-dependent DCs failed to respond to αPD-1 or αPD-L1.…”
Section: Introductionmentioning
confidence: 99%